Analisis Implementasi Paperless Office (PLO) di Lingkungan Universitas Gadjah Mada Yogyakarta (Studi Kasus di Tiga Fakultas) - Haried Novriando; Lukito Edi Nugroho; Noor Akhmad Setiawan (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2012)
One important aspect that is needed to determine the successful implementation of a system is the evaluation. Evaluation is one important aspect that is needed to figure out the successful implementation of an information system. This study aims: (1) to evaluate the use of System Paperless Office in University Gadjah Mada by using Delone and Mclean, (2) to proceed the survey data by using Partial Least Square (PLS) software for measuring user perceptions of the PLO. The data which have been collected are primary data by using questionnaires that has to be fulfilled by Gadjah Mada University employees of three faculties. Moreover, they have to be PLO users who actively use this system. The variables used are the system quality, information quality, service quality, user satisfaction, individual impact and organizational impact. The results of the survey indicate that PLO as a system has not been fully used by all PLO users. Some factors that hinder the utilization of PLO are the lack of information and system quality, so the users cannot maximize the advantage of the PLO. It also affects to the value of utility PLO.